A Grammar of the Ethics of John Reading the Letters of John from an Ethical Perspective. Volume 2 - van der Watt, Jan G.; van, Jan G. (Mohr Siebeck, 2023)
Eine Grammatik der Ethik des Johannes. Die Johannesbriefe aus ethischer Perspektive lesen. Band 2.
PublicationDate: 20230508
Keywords: Rechtsübersetzung -- Love in John -- Koinonia in John -- Hospitality in John -- Paraenesis in John -- Comparison of Gospel and Letters of John -- vituperation -- Neues Testament -- Array